PENYULUHAN TENTANG HIPERTENSI DI WILAYAH KERJA UPT PUSKESMAS BERNUNG PESAWARAN - Eka Trismiyana; Rahma Ellya; Setiawati Setiawati; Endah Susilawati (Universitas Malahayati Lampung, 2018)
ABSTRACT The prevalence of hypertension in Indonesia was 9.4 percent, diagnosed with health personnel or taking medication at 9.5 percent. So, there were 0.1 percent who take their own medication. Respondents who had normal blood pressure but were taking hypertension drugs were 0.7 percent. So the prevalence of hypertension in Indonesia is 26.5 percent. The purpose of this activity was increasing knowledge of participants abaout hypertension. The education was done at Wednesday, December 13, 2017. Education was done by discussing. Direct evaluation using question and answer about hypertension, causes of hypertension, signs and symptoms and also a free health check up. Therefore, education about hypertension ie needed to prevention Keywords: Hypertension, Counseling, Society.